Sasanian amulet practices and their survival in Islamic Iran and beyond - Kiyanrad, Sarah (Der Islam, 2018)
As an element of material culture and popular belief, amulets reflect the religious and cultural identity of their producers and/or wearers. However, they may also testify to centuries-old iconographical (and textual) traditions. To remain effective and to meet the prevailing religious concepts of the time, those ancient amuletic iconographies and textual elements needed to be reinterpreted. This article takes a look into continuities between Sasanian and Islamic amulet culture in Iran, focusing on the technique of binding and sealing forces referred to on many Late Antique and Islamic amulets.
Gesehen am 06.07.2018